Common Chinese Materia Medica Volume 10 - Ye, Huagu; Li, Chuyuan; Ye, Wencai; Zeng, Feiyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This tenth volume records 5 species of resin, 74 species of animals, 41 species of minerals and fossils. There are resins such as Liquidambar orientalis, Commiphore myrrha, Boswellia carterii, Garcinia hanburyi; animals such as Solenognathus hardwickii, , Cervus nippon, Scolopendra subspinipes, Cryptotympana pustulata, Agkistrodon acutus, Bombyx mori, Collocalia esculenta, Moschus moschiferus, Hippocampus kelloggi, Gekko gekko; minerals and fossils such as mercury, gypsum, alum, mirabilite, cinnabar, actinolite, calomel, keel, dens draconis, lithodes, fossilia spiriferis. In each specie, it introduces the scientific names, medicinal names, morphologies, habitats, distributions, acquisition and processing methods of these medicinal plants, the content of medicinal properties, therapeutic effects, usage and dosage of these medicinal plants, and attaches unedited color pictures and pictures of part herbal medicines of each species. This book series has 10 volumes in total, which covers over 2000 kinds of Chinese medicines that are commonly used. These volumes not only introduce the efficacy function and some prescriptions of the medicines, but also introduce the biological characteristics of them in detail with clear photos of the habitats, so that readers can identify them in the field. Apart from the growing environment, the books expound the distribution areas and other information to facilitate researches and other applications. The volumes are targeted at readers of general interests and it is also of high referential value for scientific researcher and teachers. It can be used as a guide to researchers, clinical doctors, and students in the department of pharmaceutics and traditional Chinese medicine.
Liquidambar orientalis -- Commiphore myrrha -- Boswellia carterii -- Garcinia hanburyi; animals such as Solenognathus hardwickii, Cervus nippon, Scolopendra subspinipes, Cryptotympana pustulata, Agkistrodon acutus, Bombyx mori, Collocalia esculenta, Moschus moschiferus, Hippocampus kelloggi, Gekko gecko -- minerals and fossils such as mercury, gypsum, alum, mirabilite, cinnabar, actinolite, calomel, keel, dens draconis, lithodes, fossilia spiriferis.
Keywords: Pharmacy; Medicine; Botany; Pharmacy; Clinical Medicine; Plant Science; Materia Medica